PENDIDIKAN KELUARGA SEBAGAI PENDIDIKAN PERTAMA BAGI ANAK - Anam Besari (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2022)
Family education is an effort made by parents in the form of habituation and improvisation to help children’s personal development. Family education is not just a process, but also the practice and implementation of education. This means that parents continue to carry out the value of education in the family. Although sometimes the theory is not fully understood, even most parents do not know much about the concept of family education. However, without realizing it, parents in their daily practice have carried out family functions in children’s education, because the function of the family is essentially character education, social, citizenship, the formation of a habit, and intellectual education of a child. The family as the first education has 5 functions, namely the affective function, the socialization and social placement function, the reproductive function, the economic function, the health care and maintenance function.